IMPLEMENTASI KERJA SAMA MAHASISWA MAGANG DALAM MEMBANTU TUGAS ADMINISTRATIF DAN INVENTARISASI PERPUSTAKAAN SMP - Anita Anatasya; Eni Egayanti; Nur Asisah; Cesianti Cesianti; Rhizma Destriani; Nurzaima Nurzaima (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The quality of administrative and library services determines the success of education, but staff limitations are often a major obstacle in the digitalization process. This study focuses on analyzing the implementation of student intern collaboration in assisting with administrative tasks and library inventory at SMP Negeri 1 Kendari. Using a qualitative descriptive method, the internship lasted four full months from September 2025 to February 2026. The research stages included preparation, orientation, technical staff assistance, and evaluation of the school's daily operational activities. The research findings indicate that the presence of students significantly accelerated the digitization of book collections through a barcode system and digital application input, as well as optimizing the work rhythm of correspondence and personnel administration. In addition, students contributed to special school services such as guest management and the distribution of the Free Nutritious Meal program, which became significantly more organized. The results of this implementation demonstrated a significant increase in work efficiency, data accuracy, and orderly filing of school documents. The main conclusion confirms that the collaboration between student interns and the school creates a strategic synergy that not only strengthens the operational capacity of the educational institution but also provides contextual professional experience for students. This program is very effective in transforming manual work systems into more structured ones in order to realize superior and sustainable quality of education services for the entire community through direct implementation of academic policies and strengthening library management. ABSTRAK Kualitas layanan administrasi dan perpustakaan menentukan keberhasilan pendidikan, namun keterbatasan staf sering menjadi kendala utama dalam proses digitalisasi sistem. Penelitian ini berfokus pada analisis implementasi kerja sama mahasiswa magang dalam membantu tugas administratif dan inventarisasi perpustakaan di SMP Negeri 1 Kendari. Menggunakan metode deskriptif kualitatif, pelaksanaan magang berlangsung selama empat bulan penuh sejak September 2025 hingga Februari 2026. Tahapan penelitian meliputi persiapan, orientasi, pendampingan staf secara teknis, hingga evaluasi kegiatan operasional harian sekolah. Temuan penelitian menunjukkan bahwa kehadiran mahasiswa mempercepat digitalisasi koleksi buku melalui sistem barcode dan input aplikasi digital secara signifikan, serta mengoptimalkan ritme kerja administrasi persuratan dan kepegawaian. Selain itu, mahasiswa berkontribusi dalam layanan khusus sekolah seperti pengelolaan tamu serta distribusi program Makanan Bergizi Gratis yang menjadi jauh lebih terorganisir. Hasil pelaksanaan ini membuktikan adanya peningkatan efisiensi kerja, akurasi data, dan ketertiban pengarsipan dokumen sekolah secara nyata. Simpulan utama menegaskan bahwa kolaborasi mahasiswa magang dan sekolah menciptakan sinergi strategis yang tidak hanya memperkuat kapasitas operasional lembaga pendidikan tetapi juga memberikan pengalaman profesional kontekstual bagi mahasiswa. Program ini sangat efektif mentransformasi sistem kerja manual menjadi lebih terstruktur guna mewujudkan mutu layanan pendidikan yang unggul dan berkelanjutan bagi seluruh masyarakat melalui implementasi langsung kebijakan akademis serta penguatan manajemen perpustakaan.